'Betrayed Believers': The Target of Influence of Extreme Right-Wing Minorities. Issue 1 (11th January 2018) - Chryssochoou, Xenia
Informed by Mugny's theorization on minority influence (Mugny, 1982 ;Mugny & Perez, 1991 ;Papastamou & Mugny, 1983 ), this paper discusses the ideological profile of the target of influence of a minority that does not challenge the system (such as extreme right-wing minorities), but confronts those held responsible for its disintegration. It is argued and empirically verified in a study with Greek participants (N = 333) that, in times of crisis and instability of the social order, people who believe in the core values of the system and who are frustrated by its disintegration support more extreme right-wing beliefs and violent practices than those who challenge the system or who are supporting it. The results highlight the ideological heterogeneity of the population to whom minority influence is addressed, which are discussed in the context of the rise of extreme right-wing beliefs in Greece and in Europe.